Examination of Faecal Caliform Presence in Groundwater in Ghana (A Case Study in Ketu South Municipality) - Seth Y Ahiabor; Austin D Amoako (Journal of Applied Sciences and Environmental Management)
Samples were taken from wide-dam, open wells and compared with piped city water. Well water from  both districts showed widespread contamination with faecal bacteria. This study revealed high Faecal and Total coliforms in all the samples with varying numbers. The high coliforms content of the eight hand-dug wells poses a health risk and renders the water unsuitable for human consumption. The presence of pathogenic organisms in the water could be attributed to pit latrine in the vicinity that extent their influence on these water qualities, since they are sited close to them. © JASEM